The Application of Narrative Nursing in Clinical Practice of Psychosomatic Diseases - Hou Yongmei (Disease and Health Research: New Insights Vol. 11, 2024)
Background: The incidence of psychosomatic diseases has been increasing year by year, and its impact on people’s health and lives is growing day by day. Scientific treatment and nursing can help patients with psychosomatic diseases recover. Objective: To understand the implementation and role of narrative nursing in the clinical practice of psychosomatic diseases, and to identify its main shortcomings. Methods: CNKI and PubMed were searched with the keywords "narrative nursing and psychosomatic diseases" and " narrative nursing and psychosomatic diseases". This study included studies in Chinese or English published between 2017 and 2024. Results: Forty papers were included. Narrative nursing can enhance patients’ and society’s understanding of disease-related knowledge, alleviate negative emotions of patients and their families, improve patients’ mental health status, increase their self-management efficacy, treatment compliance, and quality of life, as well as improve nurses’ work efficiency, and promote nurses’ self-growth. Conclusion: This study summarizes the application of narrative nursing in the clinical practice of psychosomatic diseases, and analyzes the role and difficulties from the perspectives of patients and their families, nurses, and various sectors of society. The results of this study have practical reference significance for promoting the rational development of narrative nursing and the scientific development of nursing work. Implication: This study highlights the potential of narrative nursing to improve patient outcomes and enhance the overall quality of care for individuals with psychosomatic diseases.